blue print for your Library marketing Plan - PATRICIA H. FISHER , MARSEILLE M. PRIDE (AMERICAN LIBRARY ASSOCIATION, 2006)
Marketing is about bringing them in and bringing them back. The competition understands this and pursues repeat business. Librarians can no longer afford to leave getting repeat customers to either chance or goodwill. Libraries are in danger of becoming irrelevant relics rather than the key players in the New World order that we believe they should be.Marketing is a stance and an attitude that focuses on meeting the needs of users. Marketing is a means of ensuring that libraries, librarians, and librarianship are integrated into both today’s and tomorrow’s emerging global culture.Marketing is not separate from good practice. It is good practice. Some librarians already know many of the steps needed to take a marketing approach to library operations and services. Library literature over the past fifteen to twenty years has numerous entries on the benefits of using a marketing approach in the delivery of library services. But many of these articles focus on the promotions and public relations aspects of the process and in so doing tend to miss the forest for the trees. Many librarians do not realize that marketing touches every aspect of delivering library service; they are performing marketing functions without realizing it.